TiO2 nanotubes enriched with calcium, phosphorous and zinc: promising bio-selective functional surfaces for osseointegrated titanium implants. Issue 78 (25th October 2017) - Alves, S. A.; Ribeiro, A. R.; Gemini-Piperni, S.; Silva, R. C.; Saraiva, A. M.; Leite, P. E.; Perez, G.; Oliveira, S. M.; Araujo, J. R.; Archanjo, B. S.; Rodrigues, M. E.; Henriques, M.; et al.
Abstract : TiO2 nanotubes enriched with Ca, P, and Zn by reverse polarization anodization, are promising bio-selective functional structures for osseointegrated titanium implants. Abstract : The lack of osseointegration and implant-related infections are two major complications leading to failure of dental and orthopedic implants. Therefore, the development of effective titanium (Ti) implant surfaces able to display enhanced osteogenic activity and antimicrobial properties is required. In particular, titanium dioxide (TiO2 ) nanotubes (NTs) have demonstrated promising features to modulate biological responses, as they may be easily tailored to achieve multiple functions. This work aims to study the ability of bio-functionalized TiO2 NTs to induce osseointegration, and concomitantly, to avoid infection. TiO2 NTs were bio-functionalized with calcium (Ca), phosphorous (P) and zinc (Zn), by reverse polarization anodization. Morphological and topographical features of NTs were observed through scanning electron microscopy (SEM), while surface chemistry was investigated by X-ray photoelectron spectroscopy (XPS). Biocompatibility studies were conducted with MG-63 and human mesenchymal stem cells (hMSCs) through MTT assay. Furthermore, cell morphology and cytoskeleton organization were observed by SEM and laser scanning confocal microscopy (LSCM). The osteoblastic differentiation capacity of hMSCs was studied by real-time PCR, as well as their angiogenesis ability by measuring the total release of vascular endothelial growth factor (VEGF). Finally, viability of Staphylococcus aureus ( S. aureus ) was assessed by live/dead bacterial viability assay. Results show that bio-functionalized TiO2 nanotubular surfaces are biocompatible and modulated cell morphology. In particular, NTs enriched with Ca, P, and Zn, induced to significantly up-regulated levels of bone morphogenetic protein 2 (BMP-2) and osteopontin (OPN) genes of hMSCs, when compared to conventional NTs. TiO2 nanotubular surfaces induced hMSCs to release a higher amount of VEGF, and significantly reduced the bacterial viability, both when compared to adequate Ti controls. In conclusion, the superimposition of TiO2 nanotubular-textured surfaces and their enrichment with Ca, P, and Zn, is a very promising approach for the development of novel bio-selective implant surfaces able to improve osseointegration and avoid infection.